Role of miRNA125 in Gene Regulation and Therapeutic Potential in Diseases - Baqer, Noor Abdul Hussein Kazem; Ahmed, Haneen Thamer Qadori; Obaid, Haya Ali Hussein; Jabr, Firdous Hashem Maktoof; Yaqub, Rusul Aliwy Kareem (American Journal of Biology and Natural Sciences, 2025)
The discovery of microRNAs (miRNAs) has revolutionized our understanding of gene regulation, influencing physiological and pathological processes from embryonic development to cancer progression. Despite extensive research, the mechanisms by which miRNAs modulate these complex systems remain inadequately understood, revealing a significant knowledge gap. This study employs a comprehensive literature review and data analysis to explore the roles of miRNAs in development and disease, with a focus on their potential as biomarkers and therapeutic targets. Findings highlight unique miRNA signatures in various diseases, offering insights into their diagnostic and therapeutic implications. These results underscore the necessity for continued research into miRNA functionality and delivery systems for disease intervention.